2019
DOI: 10.3390/nano9030459
|View full text |Cite
|
Sign up to set email alerts
|

Cholic Acid-Conjugated Methylcellulose-Polyethylenimine Nano-Aggregates for Drug Delivery Systems

Abstract: Cholic acid-conjugated methylcellulose-polyethylenimines (MCPEI-CAs) were synthesized and characterized for drug delivery systems. Their synthesis was confirmed by 1H NMR and FT-IR analysis. Induced circular dichroism result with Congo red showed that methylcellulose (MC) and polyethylenimine-grafted cationic derivative (MC-PEI) would have helical conformation and random coil structure, respectively. It was found that MCPEI-CAs could form positively charged (>30 mV Zeta-potential) and spherical nano-aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…NDDS has several advantages over the traditional pattern of drug administration. [27][28][29] First, the encapsulated ICG by nanomaterials could be rescued from nonspecific binding to plasma proteins, thus increasing its half-life in vivo. Second, the passive targeting delivery, which is associated with enhanced permeability and retention (EPR) effect and transcytosis (perhaps with other unknown mechanisms), makes it possible for nanomaterials within a specific size range to selectively pass through and retain in the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…NDDS has several advantages over the traditional pattern of drug administration. [27][28][29] First, the encapsulated ICG by nanomaterials could be rescued from nonspecific binding to plasma proteins, thus increasing its half-life in vivo. Second, the passive targeting delivery, which is associated with enhanced permeability and retention (EPR) effect and transcytosis (perhaps with other unknown mechanisms), makes it possible for nanomaterials within a specific size range to selectively pass through and retain in the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al prepared CA conjugates of methyl cellulosepolyethylenimines (MCPEI-CAs) nano-architecture. [66] In this report, they have shown the modulation of helicity, charge density, aggregation behavior as well as drug loading efficacy of MCPEI polymer after CA attachment. In another report, Gong and colleagues have synthesized CA derived star-shaped poly (lacticco-glycolic acid) (PLGA)-polyethylene glycol (PEG)-lactobionic acid (LA) polymer and fine-tuned the liver targeting potency of their as-synthesized polymeric nanoparticle.…”
Section: Design Trends Of Cholic Acid-based Polymersmentioning
confidence: 71%
“…However, without proper delivery systems possessing solvation and targeting ability, DOX concentration would be found to be very low in tumor tissue under in vivo conditions. It was also reported that free DOX could induce serious heart damage [45] and multi-drug resistance (MDR) of cancer cells could decrease the therapeutic effect by exporting internalized free DOX molecules [46] and that DOX-loaded nanocarriers could overcome MDR of cancer cells [47,48].…”
Section: Resultsmentioning
confidence: 99%